Non-ST Elevation Myocardial Infarction and Severe Peripheral Artery Disease in a 20-Year-Old with Perinatally Acquired Human Immunodeficiency Virus Infection. (1st April 2018) - Sharma, Purva; Kabach, Mohamad; Sehatbakhsh, Samineh; Tharpe, Rashida; Isaac, Shaun; Chait, Robert; De Almeida, Kleper
Abstract : Human immunodeficiency virus (HIV) infection confers an increased risk of cardiovascular disease, including acute coronary syndrome (ACS). Patients with perinatally acquired HIV may be at increased risk due to the viral infection itself and exposure to HAART in utero or as part of treatment. A 20-year-old female with transplacentally acquired HIV infection presented with symptoms of transient aphasia, headache, palpitations, and blurry vision. She was admitted for hypertensive emergency with blood pressure 203/100 mmHg. Within a few hours, she complained of typical chest pain, and ECG showed marked ST depression. Troponin I levels escalated from 0.115 to 10.8. She underwent coronary angiogram showing 95% stenosis of the right coronary artery (RCA) and severe peripheral arterial disease including total occlusion of both common iliacs and 95% infrarenal aortic stenosis with collateral circulation. She underwent successful percutaneous intervention with a drug-eluting stent to the mid-RCA. Patients with HIV are at increased risk for cardiovascular disease. Of these, coronary artery disease is one of the most critical complications of HIV. Perinatally acquired HIV infection can be a high-risk factor for cardiovascular disease. A high degree of suspicion is warranted in such patients, especially if they are noncompliant to their ART.